Pengaruh Kompetensi Aparatur Desa, Sistem Pengendalian Internal, Moral Sensitivity dan Budaya Organisasi terhadap Pencegahan Fraud dalam Pengelolaan Keuangan Desa (Studi Empiris pada Desa Se-Kecamatan Bansari Kabupaten Temanggung) - Novia Nurul Chalida; Yulinda Devi Pramita; Betari Maharani (Prosiding University Research Colloquium, 2022)
This study aims to test and analyze empirically the influence of village apparatus competence, internal control system, moral sensitivity, and organizational culture on fraud prevention in village financial management (empirical study in villages in Bansari District, Temanggung Regency). The data used in this study is primary data. The population of this research is 12 village offices in Bansari District, Temanggung Regency. While the samples in this study were the village head, village secretary, village finance chief/treasurer, and the activity driving team (TPK). The sampling technique used was purposive sampling method. The number of samples used is 12 village offices with a total of 47 respondents. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that the competence of village officials and moral sensitivity affect the prevention of fraud in village financial management. While the internal control system and organizational culture have no effect on fraud prevention in village financial management.